ZAKAT MANAGEMENT IN INDONESIA BASED ON THE LAW NO. 23, 2011 ACCORDING TO MAQASID ASH-SHARI'AH PERSPECTIVE OF IMAMxASHx-xSYATIBIx (W.x790 H/1388) - Qorib, Ahmad; Saidurrahman, Saidurrahman; Akbar, Ali (State Islamic University of North Sumatra Indonesia, 2025)
This study aims to determine the management of zakat in Indonesia according to Law Number 23, 2011 in the perspective of maqasid ash-Shari'ah Imam ash-Syatibi, with normative qualitative research methods carried out by examining the content of the materials used available in libraries and zakat institutions. The results of this study indicate that the management of zakat in Indonesia in Law Number 23, 2011 is not in accordance with the perspective of maqasid ash-Shari'ah Imam ash-Syatibi and the management of zakat in North Sumatra both individuals and companies according to Law Number 23, 2011 also not in accordance with the maqasid shari'ah perspective of Imam ash-Syatibi. Therefore, a review of zakat management regulations is needed to optimize zakat empowerment for both individuals and companies. Keywords: Management, Zakat, Maqasid, Sharia